Using visual-interactive properties to support data quality visual assessment on abstract and timeless data - Borovina Josko, João Marcelo; Ferreira, João Eduardo (Journal of Information and Data Management, 2021)
Visualization systems belong to supervised tools that can make noticeable the intrinsic structures of defects on data. However, despite the significant number of these systems that assist Data Quality Assessment, few provide resources to examine these structures deeply. This situation prevents data quality appraisers from using their contextual knowledge to confirm or refute any data defect. This article explores a visualisation system’s additional features and design characteristics (named V is4DD) that uses visual-interactive properties to support data quality visual assessment on abstract and timeless data (e.g., Customer, Billing). Additionally, we conduct a full review and outline the state-of-art visualization systems related to data quality assessment and fit Vis4DD into this scenario.